Kueneza Injili kwa methali - Sybertz, Donald; Healey, Joseph G. (Peramiho [Tanzania] : Benedictine Publications Ndanda, 1984)
On spreading the gospel through use of indigenous proverbs. In this case, Sukuma proverbs are used to illustrate Biblical messages.
Includes bibliographical references (p. 77) and index.
In Swahili, with some English and Sukuma.
Keywords: Homiletical illustrations; Proverbs, Sukuma; Swahili language -- Texts